Nanofluid of magnetic‐activated charcoal and hydrophobic deep eutectic solvent: Application in dispersive magnetic solid‐phase extraction for the determination and preconcentration of warfarin in biological samples by high‐performance liquid chromatography. (11th April 2021) - Nooraee Nia, Negar; Hadjmohammadi, Mohammad Reza
Abstract: In this study, for the first time, nanofluid of magnetic‐activated charcoal and hydrophobic deep eutectic solvent (AC@Fe3 O4 –DES) based dispersive magnetic solid‐phase extraction was successfully applied for the determination and preconcentration of warfarin in plasma and urine samples. The hydrophobic DES was prepared by mixing tetramethylammonium chloride (as hydrogen bond acceptor) and thymol (as hydrogen bond donor) and acted simultaneously as both carrier and stabilizer for magnetic nanoparticles. In this method, the nanofluid as a new extraction solvent was rapidly injected into the aqueous sample, which led to improvement of the mass transfer of the analytes into the sorbent and reduction of the extraction time. In the screening step, the fractional factorial design was applied for selecting some important parameters which significantly affected the extraction procedure. The effective parameters were then optimized by Box–Behnken design. Under the optimal conditions, the limits of detection were in the range of 0.3–1.6 ng/ml. A good linear range was observed in the range of 1.0–500.0 ng/ml for water and 5.0–500.0 ng/ml for urine and plasma. The intra‐ and inter‐day relative standard deviations were 2.7–3.2 and 1.9–4.5% for five replications, respectively. Based on the results, the proposed method was successfully applied for the determination of warfarin in biological samples, using high‐performance liquid chromatography.